Faculty perceptions on objective structured clinical examin dental education = Percepción de los profesores sobre el examen clínico estructurado y su objetivo en la educación dental - Wali, Othman
Structured Clinical Exam (OSCE) uses standardized content and procedures to assess students across multiple domains of learning. The study is aimed to assess knowledge, attitudes, practices and observations of dental faculty on OSCE. The survey was distributed into dental faculty members in randomly selected government and private institutions in Saudi Arabia. The questionnaire was pre-tested and consisted of 4 categories including general characteristics of respondents, knowledge on utility of OSCE in curriculum and it's reliability, attitudes regarding OSCE on a 5 point Likert scale, practices and observations on OSCE on Multiple choice questions (both single answer and multiple answer) and responses on a 5 point Likert scale. The sample size was determined to be 93 and the survey was sent electronically to 10 institutes. 101 complete responses from 7 institutions were considered from the 122 received. Faculty participation in OSCE was high within evaluators 94% (n=94) and administrators 61% (n=61). Majority of respondents (62%) believed that OSCE is most suited for competency based education, to assess cognitive skills (73%) and diagnostic interpretation (79%). Reliability of OSCE can be increased by standardization of evaluators (77%) with highest number believing that 6-8 stations (42%) are the minimum required in an OSCE. Institution guidelines (49%) coupled with workshops (47%) was the preferred method of preparation for OSCE. Majority felt that OSCE is most suitable for high stakes exams (mean=3.37) and it is an indispensable part of dental assessment (mean=3.78). Minimum number of stations for adequate reliability was reported to be lesser that in reported literature, specially so for high stakes assessments. Logistics required for arranging an OSCE and difficulty in standardized patients, may suggest that OSCE should be used in select situations.